CAV1 promotes epithelial-to-mesenchymal transition (EMT) and chronic renal allograft interstitial fibrosis by activating the ferroptosis pathway - Han, Qianguang; Ni, Bin; Bao, Wei; Zhang, Junqi; Zheng, Ming; Miu, Jinxu; Wang, Zijie; Yuan, Jingwen; Tao, Jun; Han, Zhijian; Gu, Min; Ju, Xiaobing; et al. (Frontiers in Immunology, 2025)
BackgroundChronic allograft dysfunction (CAD) stands as a critical factor that limits the long-term viability of transplanted kidneys. Ferroptosis is an iron-dependent form of programmed cell death increasingly linked to chronic fibrosis. However, the mechanism by which ferroptosis contributes to the onset and progression of CAD remains unclear.MethodsThis study analyzed transcriptome data from renal transplant biopsy samples in the Gene Expression Omnibus (GEO), through clinical samples, animal models, and cell experiments, this study investigated the mechanism by which Caveolin-1 (CAV1) promotes CAD through the regulation of the ferroptosis pathway.ResultsThe elevated levels of CAV1 were found to positively correlate with CAD incidence. Clinical and animal model validation confirmed heightened CAV1 expression in CAD. In vitro experiments demonstrated that CAV1 can directly promote chronic renal allograft interstitial fibrosis by regulating ferroptosis in renal tubular epithelial cells; additionally, it can promote epithelial-to-mesenchymal transition (EMT) by secreting Interleukin- 6 (IL-6), thereby further contributing to CAD.ConclusionCAV1 plays a critical role in the development of CAD by promoting EMT and chronic renal allograft interstitial fibrosis through the ferroptosis pathway. Adjusting ferroptosis by altering the expression abundance of CAV1 may become an important method for the prevention and treatment of CAD in the future.